Effect of the dilaton field and plasma medium on deflection angle by black holes in Einstein-Maxwell-dilaton-axion theory - Javed, W.; Babar, R.; Övgün, Ali (Amer Physical Soc, 2019)
In this paper, we argue that one can calculate the weak deflection angle of light in the background of an Einstein-Maxwell-Dilaton-axion black hole using the Gauss-Bonnet theorem. To support this, the optical geometry of the black hole and the Gibbons-Werner method is used to obtain the deflection angle of light in the weak-field limits. Moreover, we investigate the effect of a plasma medium on the deflection of light for a given black hole. Because the dilaton and axion are candidates for dark matter, this can give us a hint about the observation of the dark matter that is supported by the black hole. Hence, we demonstrate the observational viability by showing the effect of dark matter on the weak deflection angle of light.
Keywords: Dark-Matter; Invariance; Cosmology